A Dynamic Bandwidth Allocation Algorithm for IEEE 802.11e WLANs with HCF Access Method - Gennaro Boggia; Pietro Camarda; Claudio Di Zanni; Luigi Grieco; Saverio Mascolo; Gunnar Karlsson; Michael Smirnov (Quality for All, 2003)
This paper proposes a dynamic bandwidth allocation algorithm for supporting QoS in IEEE 802.11e WLANs with Hybrid Coordination Function (HCF) access method. It distributes the limited WLAN capacity by taking into account the desired queueing delay that multimedia data flows would expect. The algorithm has been designed by following a control theoretic approach and its properties have been analytically investigated. The effectiveness of our approach has been also proved by computer simulations, involving both audio and video flows. Both mathematical analysis and simulation results show that the algorithm guarantees queueing delays that are bounded by the QoS specifications.